2020
DOI: 10.20473/jbe.v8i12020.8-15
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profiles of Vitiligo With Narrowband Uvb and Topical Corticosteroid Therapy at Dr. Soetomo Hospital

Abstract: Background: Vitiligo is a depigmenting disorder that causes a loss of melanocytes in the epidermis. Treatment preferences are based on the characteristics of the vitiligo lesions. Purpose: This study evaluates the clinical profiles of vitiligo treated with narrowband UVB (NB-UVB) radiation and topical corticosteroid therapy in Dr. Soetomo Hospital in 2017. Methods: This study is a retrospective study that uses data from the medical records of vitiligo patients who were treated with NB-UVB radiation and topical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Fauzia's research in 2017 at the Medical Cosmetics Division of the Dermatology and Venereology Outpatient Clinic at Dr. Soetomo General Hospital revealed that the age groups with the newest vitiligo patients were 20-44 years and 45-59 years, with 12 (32.4%) patients each. 8 These finding back up the researchers' findings that the majority of vitiligo patients were young adults. These study results are consistent with the findings of Suseno, who conducted research at Cipto Mangunkusumo General Hospital in Jakarta between 2015 and 2017.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Fauzia's research in 2017 at the Medical Cosmetics Division of the Dermatology and Venereology Outpatient Clinic at Dr. Soetomo General Hospital revealed that the age groups with the newest vitiligo patients were 20-44 years and 45-59 years, with 12 (32.4%) patients each. 8 These finding back up the researchers' findings that the majority of vitiligo patients were young adults. These study results are consistent with the findings of Suseno, who conducted research at Cipto Mangunkusumo General Hospital in Jakarta between 2015 and 2017.…”
Section: Discussionmentioning
confidence: 78%
“…10 In 2017, researchers at Dr. Soetomo General Hospital Surabaya discovered 19 (51.4%) female patients. 8 In a study conducted at Dr. Cipto Mangunkusumo General Hospital in Jakarta, it was discovered that more female patients (55.3%) visited the doctor about their lesions than male patients. 9 Although both men and women appear to be affected equally by vitiligo, there are significant gender differences in the patterns of mental and social impairments.…”
Section: Discussionmentioning
confidence: 99%
“…4 Additionally, female patients tend to have more cosmetic concerns and have more free time for longterm therapy. 5 Age group representation revealed that 26.92% of respondents were between the ages of 0-14 years, 26.92% were between the ages of 15-24 years, 38.5%…”
Section: Discussionmentioning
confidence: 99%
“…(Indonesia, 2020) discovered nearly the same pattern in Surabaya, where people between the ages of 45 and 59 accounted for the bulk of instances. 5 Lesions were considered active if it had developed during the previous year, had a trichrome color, and showed signs of the Koebner phenomenon. 1 From the total number of patients, 22 had stable vitiligo lesions, and 4 had unstable lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation